An IgG subclass imbalance in connective tissue disease. - Kay, R A (1988)
A group of 16 patients with a disproportionate polyclonal increase in their serum IgG1, resulting in raised concentrations of total IgG immunoglobulin, has been discovered. The other IgG subclasses in these patients are either normal or slightly reduced, resulting in an IgG1:IgG2 ratio of at least 10:1. Most cases are marked by the presence of anti-extractable nuclear antigen (anti-ENA) antibodies and high titres of rheumatoid factor and antinuclear antibody. All but one patient has a connective tissue disease, nearly twice the prevalence found in similarly hypergammaglobulinaemic patients without this IgG subclass imbalance. Among patients with systemic lupus erythematosus (SLE), those with the IgG1 disorder have a higher prevalence of high titre rheumatoid factor and antinuclear antibody, but a lower prevalence of anti-double-stranded DNA (anti-dsDNA) antibodies above 30 U/ml. It is suggested that this immunoglobulin abnormality may reflect a unique immunoregulatory dysfunction in these patients.